Association Analysis of Neuronal Nitric Oxide Synthase 1 Gene Polymorphism With Psychopathological Symptoms in Chronic Ketamine Users - Chen, Jiansong; Zhang, Minling; Zhou, Chao; Ding, Yi; Fan, Ni; He, Hongbo (Frontiers in Psychiatry, 2020)
Objective: We previously found that chronic ketamine usages were associated with various psychotic and cognitive symptoms mimicking schizophrenia. The blockade of the NMDA receptor and subsequent nitric oxide synthase 1 (NOS1) dysfunction were found to be closely correlated with schizophrenia including NOS1 gene polymorphisms. We examined the allelic variants of the gene coding neuronal nitric oxide synthase 1 (NOS1) in chronic ketamine users in the Chinese population and analyzed the association between NOS1 gene polymorphism and psychopathological symptoms in chronic ketamine users. The association between the NOS1 polymorphism and ketamine use characteristics was also examined. Methods: One hundred ninety seven male chronic ketamine users and 82 controls were recruited. Four common SNPs of the NOS1 gene, rs6490121, rs41279104, rs3782206, and rs3782219, were examined by real-time PCR with the TaqMan® assay system. Psychopathological symptoms were assessed using the Positive and Negative Syndrome Scale (PANSS), Beck Depression Inventory (BDI), and the Beck Anxiety Inventory (BAI). Results: The genotype distribution of rs6490121 and rs41279104 in chronic ketamine users was significantly different from that in the control (p = 0.0001 and p = 0.002). The G allele frequency of rs6490121 in ketamine users was higher than that in the control (p = 2.23 * 10−6, OR = 3.07, 95% CI = 1.93–4.90). The T allele frequency of rs41279104 in chronic ketamine users was higher than that in the control (p = 0.01, OR = 1.76, 95% CI = 1.14–2.72). The BAI score was significantly different among the three genotypic groups of rs6490121 (F = 6.21, p = 0.002) in ketamine users; subjects of genotype AG and GG had a lower score than subjects of genotype AA. The score of the negative symptom subscale of PANSS was significantly different among the three genotypic groups of rs41279104 (F = 5.39, p = 0.005); in ketamine users, subjects of genotype CT and TT had a higher score than subjects of genotype CC. There was no difference in drug use characteristics in different genotypes of the four NOS1 gene polymorphisms tested in ketamine users (p > 0.05).